Methodological Workshop “Multicultural Education: American Experience and Its Interpretation in Ukrainian Context” (October, 10, 2013) - Gorbunova, Lyudmila (Filosofiya osvity. Philosophy of Education, 2013)
The workshop was devoted to the problems and practices of multicultural education in the USA, which were presented in a special report. The necessity for study American experience in this area increased as far as education become strategic resource of development of Ukrainian society according to the global challenges of the 21st century and local socio-cultural and political needs. Educational integration of Ukraine to EU needs clarification of the content of multicultural challenges, the modes of its interpretation and theoretical verification of the possible responses on them. The issues of comparison and correlation of cultures, the boundaries of the accepting of the culture of others; the problem of tolerance as an acceptance of others and a dialogue as a form of politics of acceptance were discussed in such context. It was mentioned that Ukraine has its own and unique experience of multicultural society and its authentic traditions of multicultural education. A caution against possibility of transformation of multiculturalism in a kind of market of ethical values and traditions were also claimed. The necessity of creative openness of Ukraine towards experience of others and multicultural education in particular were also stressed. The most important mode of multiculturalism is the sensitivity toward substantial cultural peculiarities. The challenges of multiculturalism and its implementation require re-thinking the theoretical model of human being, especially from the viewpoint of anthropological boundaries, oriented on the depicting of limits of “human”. The very central idea of anthropological multiculturalism is an equal dialogue of cultures as a background of contemporary society and dialogism as a common principle of coexistence of peculiarities in contemporary world of cultural diversity. It was stressed that dialogically organized civil society of deliberative democracy practices not a static, but interactive and dynamic multiculturalism. The establishing of multidimensional responsibility for creation the global culture of peace within global cultural and institutional structures needs to be fundamental for multicultural education.